Neuro-Linguistic Programming as Tool of Self-Actualisation of Individual and Reflection in the Autopoietic Organisation (Journal of Universal Excellence, 2026)
Research Question (RQ): The concept of self-actualisation of personal growth presumes each person has a kind of internal strength, which leads that individual to their growth, learning, improvement and change. The actualisation of a person’s potential allows for creativity and growth, respecting the person here and now, emphasising the “self” and granting value to an experience. We studied neuro-linguistic programming tools to determine how they influence the self-actualization of an individual in an autopoietic organization.Purpose: The purpose of this research is determining the principle of self-management as an element of autopoietic organisation based of self-actualisation and personal growth with the tools of neuro-linguistic programming. The aim of this research is the interpretation of the factors of the neuro-linguistic programming, which influence the self-actualisation of personal growth as an element of autopoietic organisation.Method: The goals of this research are reached with a triangulation of the research in the field of literature, the range of self-actualisation of personal growth and a qualitative research of the factors of neuro-linguistic programming, which influence the self-actualisation of personal growth as an element of autopoietic organisation.Results: The range of self-actualisation of personal growth exhibits a preference of tools of neuro-linguistic programming. The qualitative research connects the elements of an autopoietic organisation with the tools of neuro-linguistic programming. We introduce a suggestion for the management of the autopoietic organisation principle for the self-actualisation of personal growth with the tools of neuro-linguistic programming.Organisation: The organisation requires concrete explanation of the operation of the principle in the field of self-actualisation of an autopoietic organisation. The main characteristic is the reciprocal dynamics, which is self-renovating, self-developing and self-learning. It influences the management.Society: The findings of the research encourage individuals to self-management and self-treatment according to the self-actualisation of personal growth.Originality: The original approaches to the influence of neuro-linguistic programming on self-management and co-management in an autopoietic organisation are researched.Limitations/Further Research: Due to the originality of the research we suggest a research of larger extent with the same methodology.
Keywords: autopoietic organisation; self-actualisation; neuro-linguistic programming; co-management; qualitative research; triangulation; personal growth; empirical research